Students' opinions on welfare and ethics issues for companion animals in Australian and New Zealand veterinary schools. Issue 6 (June 2017) - Degeling, C; Fawcett, A; Collins, T; Hazel, S; Johnson, J; Lloyd, J; Phillips, CJC; Stafford, K; Tzioumis, V; McGreevy, P
Abstract : Objective: To determine what veterinary students in Australia and New Zealand consider important competences in companion animal welfare and ethics (AWE) required on their first day of practice, and to explore how their priorities relate to gender and stage of study. Methods: Undergraduate students at all veterinary schools in Australia and New Zealand were sent an online survey. A subset of questions required participants to rank the importance of preselected AWE topics pertaining to companion animals. Data were analysed to determine differences in the way students of different gender or academic stage prioritised each of these AWE topics. Results: Of 3220 currently enrolled students, 851 participated in the survey: 79% were female, 17% male, 4% unspecified. Ranking of the AWE topics, from highest to lowest importance, was: neutering, companion animal husbandry, euthanasia, behaviour and training, animal breeding, over‐servicing in relation to animal needs and cosmetic surgery. Female students consistently ranked competency in AWE issues surrounding neutering more highly than male students (P = 0.006). Students in senior years of study ranked the importance of competency in animal abuse/hoarding (P = 0.048), shelter medicine (P = 0.012) and animal breeding (P = 0.002) less highly than those in junior years. Conclusions: Australasian veterinary students placed more importance on competency in AWE issues associated with clinical practice (such as neutering and euthanasia) than on professional behaviours (such as over‐servicing and animal breeding). However, we consider that emphasis should still be placed on developing graduate competency in the latter categories to reflect growing societal concerns about companion animal over‐supply and inappropriate professional conduct.